Quantitative plasma proteomics identifies metallothioneins as a marker of acute-on-chronic liver failure associated acute kidney injury - Acharya, Pragyan; Saha, Rohini; Quadri, Javed Ahsan; Sarwar, Saba; Khan, Maroof Ahmad; Sati, Hem Chandra; Gauniyal, Nidhi; Shariff, Ahmadullah; Swaroop, Shekhar; Pathak, Piyush; Shalimar, (Frontiers in Immunology, 2023)
Background Acute kidney injury (AKI) considerably increases the risk of short-term mortality in acute-on-chronic liver failure (ACLF) but predicting AKI is not possible with existing tools. Our study aimed at de novo discovery of AKI biomarkers in ACLF. Methods This observational study had two phases- (A) Discovery phase in which quantitative proteomics was carried-out with day-of-admission plasma from ACLF patients who initially had no-AKI but either progressed to AKI (n=10) or did not (n=9) within 7 days of admission and, (B) Validation phase in which selected biomarkers from the discovery phase were validated by ELISA in a larger set of ACLF plasma samples (n=93) followed by sub-group analyses. Results Plasma proteomics revealed 56 differentially expressed proteins in ACLF patients who progressed to AKI vs those who did not. The metallothionein protein-family was upregulated in patients who progressed to AKI and was validated by ELISA as significantly elevated in both- (i) ACLF-AKI vs no-AKI (p-value ≤ 0.0001) and (ii) progression to AKI vs no-progression to AKI (p-value ≤ 0.001). AUROC for AKI vs no-AKI was 0.786 (p-value ≤0.001) and for progression to AKI vs no-progression to AKI was 0.7888 (p-value ≤0.001). Kaplan-Meier analysis revealed that ACLF patients with plasma MT concentration >5.83 ng/mL had a high probability of developing AKI by day 7 (p-value ≤0.0001). High expression of metallothionein genes was found in post-mortem liver biopsies of ACLF patients. Conclusion Day-of-admission measurements of plasma metallothionein can act as predictive biomarkers of AKI in ACLF.